Education of Type 2 DM Patients on Dietary Adherence in The Working Area of The Public Health Center in Solok City - Sumarni, Tintin; Yulastri; Noviherawati (POLTEKKES KEMENKES PADANG, 2024)
The prevalence of diabetes mellitus increased significantly from 6.9% in 2013 to 8.5% in 2018. Adherence to DM management can maintain blood glucose stability which is very important for the survival of patients with type 2 DM. Patients with DM are at risk of microvascular damage such as retinopathy and nephropathy which reduce the quality of life of patients. The purpose of this study was to determine the effect of coaching education using the P3DM module on the compliance of Type II DM patients in dietary management. This research design was quasi-experimental with a pre-post test control group design. The study population was type 2 DM patients who lived in the Solok city health center work area, with a sample of 41 respondents. intervention and 41 control respondents. The intervention was provided in the form of coaching education using the P3DM module for six meetings for two months. The results showed an increase in dietary compliance in the intervention and control groups with a value of p = 0.00., coaching education using the P3DM module has an effect on compliance with dietary management. The t value in the intervention group obtained was greater than the control group. Coaching education using the P3DM module provides an advantage as a complement to the educational program in improving compliance with the management of DM patients.